2022
DOI: 10.1002/ccd.30248
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in patients with uninterrupted vitamin K antagonists

Abstract: Background Bridging of vitamin K antagonist (VKA) with heparin is usually not promoted during interventional or surgical procedures related to increased risk of bleeding and thrombotic events but this strategy has not been evaluated during transcatheter aortic valve implantation (TAVI). Purpose The aim of this study was to evaluate the rate of major bleeding and vascular complications after TAVI performed in patients with uninterrupted VKA. Methods From January 2016 to October 2017, consecutive patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the BRAVO-3 trial, it was found that among patients with PAD, anticoagulation with bivalirudin does not reduce the risk of bleeding or vascular complication when compared to unfractionated heparin, which is the standard anticoagulation used in most centers ( 19 ). Among patients who have an alternative indication for vitamin K antagonist, it was found that uninterrupted warfarin therapy among patients with PAD was associated with a drastically high risk of vascular complication when compared to those who had no PAD, with a relative risk of 10.95 ( 20 ).…”
Section: Anticoagulation Strategymentioning
confidence: 99%
“…In the BRAVO-3 trial, it was found that among patients with PAD, anticoagulation with bivalirudin does not reduce the risk of bleeding or vascular complication when compared to unfractionated heparin, which is the standard anticoagulation used in most centers ( 19 ). Among patients who have an alternative indication for vitamin K antagonist, it was found that uninterrupted warfarin therapy among patients with PAD was associated with a drastically high risk of vascular complication when compared to those who had no PAD, with a relative risk of 10.95 ( 20 ).…”
Section: Anticoagulation Strategymentioning
confidence: 99%
“…In this issue of CCI, 3 Robert et al analyzed data from an observational, prospective, monocenter registry, including 88 patients with an indication for long‐term OAC who underwent TAVI between January 2016 and October 2017. The median STS score was 5.1 and the main reason for long‐term OAC was atrial fibrillation (90%).…”
mentioning
confidence: 99%